2014
DOI: 10.3389/fpsyg.2013.01010
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive training with casual video games: points to consider

Abstract: Brain training programs have proliferated in recent years, with claims that video games or computer-based tasks can broadly enhance cognitive function. However, benefits are commonly seen only in trained tasks. Assessing generalized improvement and practicality of laboratory exercises complicates interpretation and application of findings. In this study, we addressed these issues by using active control groups, training tasks that more closely resemble real-world demands and multiple tests to determine transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 92 publications
4
86
0
2
Order By: Relevance
“…5 A WHO survey in 2010 found that 55% of adolescent males and 20% of females reported computer gaming more than 2 hours daily; presumably CHR individuals fall within this general range. 27 The findings on the cognitive effects of casual video games in healthy young adults are very mixed, and while some of them do appear to drive gains in visual processing and visual attentional control, some studies have shown that they are associated with changes in cognitive strategies (eg, Baniqued et al 28 ; see Shams et al 29 for a review). Furthermore, surprisingly few studies have examined the effects of video game exposure on verbal memory in either healthy or cognitively impaired individuals.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…5 A WHO survey in 2010 found that 55% of adolescent males and 20% of females reported computer gaming more than 2 hours daily; presumably CHR individuals fall within this general range. 27 The findings on the cognitive effects of casual video games in healthy young adults are very mixed, and while some of them do appear to drive gains in visual processing and visual attentional control, some studies have shown that they are associated with changes in cognitive strategies (eg, Baniqued et al 28 ; see Shams et al 29 for a review). Furthermore, surprisingly few studies have examined the effects of video game exposure on verbal memory in either healthy or cognitively impaired individuals.…”
Section: Summary Of Findingsmentioning
confidence: 99%
“…Only modest support was shown for the potential of videogame training to improve cognitive function in healthy older adults and another study revealed only specific effects [6]. The transfer of training to real life improvement was seen as offering mixed results [7][8][9]. Finally, another study revealed that an active lifestyle was more effective than the effect of short term training interventions as impacting cognitive change over time in a dementia risk group.…”
Section: Introductionmentioning
confidence: 99%
“…However, it leaves time for patients to improve their situation on their own time even while in rehabilitation centers. Games are now being sought as a means to tap into the intrinsic motivation they promote and research investigates to what degree, for example, causal games train cognitive abilities [1]. We believe that purpose-built games that provide more feedback and are simple for patients to understand are better suited for rehabilitation.…”
Section: Introductionmentioning
confidence: 99%